Analisis Kepuasan Pelanggan Dengan Importance Performance Analysis (IPA) - Palinggi, Yonathan; Sabran, Sabran; Hamji, Hamji (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
The purpose of this study was to determine customer satisfaction based on service quality and marketing mix variables using the Importance Performance Analysis Method and in which quadrant is customer satisfaction at Anyi Ethnik Stores in Tenggarong using the Importance Performance Analysis Method. The population in this study were all consumers who were directly involved and had made purchases at the Anyi Ethnic Shop in Tenggarong in August 2021 for 10 days. The total number of samples used in this study was 50 people. The results showed that there was a high level of customer satisfaction with Anyi Ethnic Shops using the Importance Performance Analysis Method where there were 6 factors Tenggarong Anyi Ethnic Shops did not provide the best service on this attribute. In order for management to concentrate on improving all of its performance on this attribute (concentrate here). The services provided to the attributes in Quadrant B need to be maintained (keep up the good work). The Anyi Ethnic Shop in Tenggarong provides good service to customers. Therefore, this area is called an excess area (possible overkill).